2021
DOI: 10.1093/jac/dkab244
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 coinfection with additional respiratory virus does not predict severe disease: a retrospective cohort study

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) claimed over 4 million lives by July 2021 and continues to pose a serious public health threat. Objectives Our retrospective study utilized respiratory pathogen panel (RPP) results in patients with SARS-CoV-2 to determine if coinfection (i.e. SARS-CoV-2 positivity with an additional respiratory vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…Some studies have found that coinfections decrease disease severity (Martin et al, 2011 , 2013 ) or are at least no more severe than mono-infections (Brand et al, 2012 ; Martin et al, 2013 ; Asner et al, 2014 ; Rotzen-Ostlund et al, 2014 ; Mexico Emerging Infect Dis, 2019 ; Xiang et al, 2021 ), although others have found that coinfections can be more severe than mono-infections (Waner, 1994 ; Goka et al, 2015 ; Alosaimi et al, 2021 ; Musuuza et al, 2021 ). In the case of SARS-CoV-2 coinfections, studies are equally mixed about the severity of clinical disease, with some studies indicating a protective effect (Chekuri et al, 2021 ; Goldberg et al, 2021 ), others showing a worsening of clinical outcomes (Alosaimi et al, 2021 ; Stowe et al, 2021 ), and still others showing no significant difference between SARS-CoV-2 coinfections and mono-infections (Cheng et al, 2021 ; Guan et al, 2021 ). A meta-analysis of SARS-CoV-2 coinfections with influenza indicated no overall increase in mortality associated with coinfections, but found that SARS-CoV-2/influenza coinfections had decreased mortality in China and increased mortality in other regions (Guan et al, 2021 ), suggesting that other factors besides the characteristics of the two pathogens might be involved in determining severity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that coinfections decrease disease severity (Martin et al, 2011 , 2013 ) or are at least no more severe than mono-infections (Brand et al, 2012 ; Martin et al, 2013 ; Asner et al, 2014 ; Rotzen-Ostlund et al, 2014 ; Mexico Emerging Infect Dis, 2019 ; Xiang et al, 2021 ), although others have found that coinfections can be more severe than mono-infections (Waner, 1994 ; Goka et al, 2015 ; Alosaimi et al, 2021 ; Musuuza et al, 2021 ). In the case of SARS-CoV-2 coinfections, studies are equally mixed about the severity of clinical disease, with some studies indicating a protective effect (Chekuri et al, 2021 ; Goldberg et al, 2021 ), others showing a worsening of clinical outcomes (Alosaimi et al, 2021 ; Stowe et al, 2021 ), and still others showing no significant difference between SARS-CoV-2 coinfections and mono-infections (Cheng et al, 2021 ; Guan et al, 2021 ). A meta-analysis of SARS-CoV-2 coinfections with influenza indicated no overall increase in mortality associated with coinfections, but found that SARS-CoV-2/influenza coinfections had decreased mortality in China and increased mortality in other regions (Guan et al, 2021 ), suggesting that other factors besides the characteristics of the two pathogens might be involved in determining severity.…”
Section: Discussionmentioning
confidence: 99%
“…Epstein–Barr virus (EBV), human herpesviruses (HHV), seasonal human coronaviruses (HCoV), adenoviruses and human metapneumovirus (HMPV) were also reported in several studies [ 490 , 549 , 552 , 555 , 556 ]. The overall effect of viral co/superinfections on the severity of COVID-19 is unclear [ 550 , 553 , 556 , 557 ], but the common phenomenon of viral interference [ 558 ], and differences between the relative proportion and effect of specific pathogens in the studies may be responsible for these mixed results.…”
Section: Host Factorsmentioning
confidence: 99%
“…However, the characteristics of RSV resurgences varied greatly. Changes in testing practices, evolution of surveillance systems, or viral interference between RSV and SARS‐COV‐2 may have contributed to these observations 13 . Also, non‐pharmaceutical interventions (NPIs) that were implemented to slow the spread of COVID‐19 likely played a role 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Changes in testing practices, evolution of surveillance systems, or viral interference between RSV and SARS-COV-2 may have contributed to these observations. 13 Also, nonpharmaceutical interventions (NPIs) that were implemented to slow the spread of COVID-19 likely played a role. 14,15 Although several countries have reported their own conclusions regarding the effect of the COVID-19 pandemic on RSV circulation, few assessed the impact of NPI policies and their timing on RSV activity.…”
Section: Introductionmentioning
confidence: 99%